Renal Replacement Therapy for Renal Transplant Recipients During ICU Stay. (July 2018) - Gedik, Ender; Sahinturk, Helin; Ozdemirkan, Aycan; Zeyneloglu, Pinar; Torgay, Adnan; Pirat, Arash; Haberal, Mehmet
Abstract : Introduction: Renal transplantation for end stage kidney disease is a definitive therapy. In the early and late postoperative period, renal transplant recipients may require renal replacement therapy (RRT) during their ICU stay. The aim of the study is to demonstrate the characteristics of patients with renal transplants who were admitted to the ICU and underwent RRT. Materials and Methods: We retrospectively screened adult renal transplant recipients (age>18 years) admitted to ICU between June 2013 to October 2017. Among them, we evaluated those who were admitted to ICU and patients were further divided into two groups according to whether they did not require RRT (Group 1, n=21) or did require RRT (Group 2, n=19). The demographic data, time to ICU admission after renal transplantation, estimated glomerular filtration rate (eGFR) and chronic kidney disease (CKD) staging score at the first and last day in the ICU were recorded and calculated from our database. Results and Discussion: There were 199 adult renal transplantations performed. Among them, 20% (n=40) were admitted to ICU. The mean age of the patients was similar (45.8 vs 45.8 years) and the majority of patients were male (85.7% vs 63.2%). The mean time between renal transplantation and ICU admission was longer in Group 1 (211.1 vs 141.7 days). The majority of transplantations were performed as living donor related (76.2% vs 47.4). There were 3 rejected grafts (14.3%) in Group 1 and 9 (47.4%) in Group 2 (p=0.023). Among them, 2 (9.5%) patients in Group 1 and 4 (21.1%) patients in Group 2 were retransplanted. The mean APACHE II score at ICU admission was similar (13.9 vs 18.0). eGFR levels at ICU admission and discharge were higher in Group 1 (15.9 vs 12.3 mL/min/1.73m2, p=0.04 and 51.5 vs 38.9 mL/min/1.73m2, p>0.05, respectively). The most frequent CKD staging score of patients at ICU admission was 4 (52.4%) in Group 1 and 5 (84.2%) in Group 2. At the last day in ICU, the CKD staging score was 3 (33.3%) in Group 1 and 5 (100%) in Group 2. The modalities of RRT were intermittent hemodialysis and continuous RRT (63.2% vs 36.8%, respectively). Incidences of sepsis, rejection, requirements for vasopressors and mechanical ventilation were significantly higher in Group 2 (p=0, p=0.023, p=0.026, p=0.028, respectively). The lengths of stay in ICU and hospital were significantly higher in Group 2 (6.8 vs 12.3 days and 64.7 vs 123.7 days, p=0.04, respectively). The groups were not different in terms of mortality. Conclusion: Our results indicate that RRT was initiated in renal transplant recipients admitted to ICU with CKD Stage 4-5 and characteristics of these patients included higher incidences of rejection, sepsis and requirements for vasopressors and mechanical ventilation.